Infection of the swim bladder parasite Anguillicoloides crassus in the European eel (Anguilla anguilla) caught from the Gediz Delta (Aegean Sea) - Salman, Alp (Ege Journal of Fisheries and Aquatic Sciences, 2023)
The wild European eels (776 fish, mean total length of 547±91 mm, mean weight 340±198 g) were obtained monthly between October 2015-September 2016 in Gediz Delta (Izmir Bay, Aegean Sea). A total of 263 nematode parasites (Anguillicoloides crassus) were isolated from the swim bladders of 52 parasitized fish. Parasitological indices were found relatively low. The prevalence was 6.7% and the mean intensity was 5.05. The abundance of A. crassus was also calculated as 0.33 in all sampled eels.